2022
DOI: 10.1111/aej.12672
|View full text |Cite
|
Sign up to set email alerts
|

Association between second mesiobuccal canal and apical periodontitis in retrospective cone‐beam computed tomographic images

Abstract: This retrospective cone‐beam computed tomography study aimed to investigate the possible associations of apical periodontitis (AP) with missed/unmissed second mesiobuccal (MB2) canals. MB2 canals and AP were investigated in 257 endodontically treated and 673 untreated maxillary molars, and the former were analyzed regarding missed/unmissed MB2 canals. The chi‐squared test and odds ratio (OR) were used for statistics. The prevalence of MB2 canals in maxillary first molars was higher than that in second molars (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
(90 reference statements)
1
1
0
Order By: Relevance
“…The above statement implies that overlooking the presence of the MB2 canal can significantly increase the likelihood of RCT failure. Our study’s findings are consistent with those of a retrospective CBCT study by Colakoglu et al that examined the potential associations between PL and missed MB2 canals [ 39 ]. The study revealed that endodontically treated maxillary molars with missed MB2 canals had a 5.5 times higher risk of PL than those without missed MB2 canals.…”
Section: Discussionsupporting
confidence: 91%
“…The above statement implies that overlooking the presence of the MB2 canal can significantly increase the likelihood of RCT failure. Our study’s findings are consistent with those of a retrospective CBCT study by Colakoglu et al that examined the potential associations between PL and missed MB2 canals [ 39 ]. The study revealed that endodontically treated maxillary molars with missed MB2 canals had a 5.5 times higher risk of PL than those without missed MB2 canals.…”
Section: Discussionsupporting
confidence: 91%
“…According to data in the literature, the missed canals involve mainly the first maxillary molars, especially the mesio-buccal 2 (MB2) canal (Figure 6), followed by the first mandibular molars, especially the second canal in the distal roots. 60,64,65 Moreover, an additional mesial canal, the middle mesial canal, in lower molars is frequently found with a percentage ranging from 0.26% to 53.8%. [66][67][68] Martins et al reported that the overall prevalence of a second canal in the lower central and lateral incisors and canines was 20.4%, 25.3%, and 5.9%, respectively, with the actual percentage strictly related to the population ethnicity as described by Dhuldhoya et al (Figure 7) 69,70 two scenarios that should be taken into consideration are the prevalence of accessory canals in upper and lower premolars and C-shaped canals in lower molars.…”
Section: Orifice Location and Missed Anatomymentioning
confidence: 99%
“…При цьому ризик розвитку апікального періодонтиту в області верхніх молярів виявився в 5,5 разів вищий при відсутності адекватного лікування саме другого мезіо-щічного каналу в порівняння із ситуаціями, коли хемо-механічна обробка такого була виконана у відповідності до загальноприйнятих протоколів [12].…”
Section: Possibilities Of Using Cone-beam Computed Tomography For Sec...unclassified